Framing of China’s Soft Power in Nepal: A Case Study of Cultural and Educational Diplomacy in the Media - Lok Bahadur B. K.; Yonghong Dai; Dipak Devkota; Ashok Poudel; Zeyar Oo (Journalism and Media)
This research conducts a comparative content analysis of two leading English-language newspapers, The Kathmandu Post and Rising Nepal, to examine the media framing of China’s cultural and educational diplomacy in Nepal. This study employs a frame analysis methodology alongside a qualitative content analysis approach to systematically examine thirty news items published from 2021 to early 2025. Key themes were coded and examined based on frequency and contextual framing, including cultural interaction, Chinese language promotion, Confucius Institute coverage, education diplomacy, and geopolitical alignment. Rising Nepal demonstrates a clear state-centric editorial stance, frequently articulating a supportive tone that emphasizes bilateral collaboration, strategic partnership, and mutual growth, thereby highlighting a significant contrast in representational patterns. This research argues that these contrasting frames signify underlying ideological and geopolitical affiliations, rather than merely editorial choices. This research contributes to the expanding body of literature on soft power, media and culture diplomacy, and the geopolitics of influence in South Asia by integrating media framing theory with qualitative analysis.